The life cycle of Echinostoma bolschewense (Kotova, 1939) (Trematoda: Echinostomatidae) - Nasincová, V (Folia parasitologica, 1991)
The life cycle of E. bolschewense, the species with 37 collar spines and closely related to E. revolutum, was experimentally studied. The following developmental stages are described: mother and daughter rediae, cercaria, metacercaria, and adult. The freshwater prosobranchiate snail Viviparus contectus was found to be the first intermediate host in nature. Under experimental conditions, the miracidia developed in V. contectus. They did not, however, penetrate into Bithynia tentaculata or into any of the pulmonate snails tested. The cercariae encysted in various Prosobranchia and Pulmonata. Adult worms were commonly obtained from hamsters (Mesocricetus auratus) and only exceptionally from chickens (Gallus gallus f. dom.). The species studied is considered to be conspecific with Cercaria bolschewensis described by Kotova (1939).
Keywords: Echinostoma; Animals; Ducks; křeček rodu Mesocricetus; kur domácí; kachny; Mesocricetus; sladká voda; křečci praví; Snails; zvířata; Chickens; Fresh Water; hlemýždi; Cricetinae